Gastrointestinal Parasite Infection on Stray Cat and Pet Cat at Blitar Regency, East Java Province - Egga Johar Praptanto; Bambang Purnomo Sunardi; Budiarto Budiarto; Agus Wijaya (Journal of Parasite Science (JoPS), 2021)
The purpose of this study was to find out the parasite species and prevalence of gastrointestinal parasite on stray cat and pet cat at Blitar. In an amount of 90 cats feces were collected from two different types of sample, those are stray cat and pet- cat from three sub-districts located at Blitar Regency. Cats feces were analyzed with native, sedimentation and float techniques. The result showed that prevalence of gastrointestinal parasite infection on cat at Blitar was amounted to 71% at stray cat and 40% at pet cat. The parasite that was found in this research are Toxocara cati, Ancylostoma sp. and Isospora sp.